Juridical review of the decision of the constitutional court number 70/phpu.bup-xxiii/2025 re-voting of the serang regency election - Hibar, Ujang; Wahyudi, Wahyudi; Asnawi, Asnawi; Saepudin, Eli Apud (IHSA Institute, 2025)
Constitutional Court Decision Number 70/PHPU.BUP-XXIII/2025 is a response to the dispute over the results of the 2024 Serang Regency Regional Head Election (Pilkada), which was marked by allegations of structured, systematic, and massive (TSM) election violations. The violations included the involvement of state officials, such as the Minister of Villages and Disadvantaged Regions Development, as well as open support from village heads for one candidate pair. This study aims to examine the legal basis and juridical considerations of the Constitutional Court in deciding to order a re-voting (PSU) in all polling stations (TPS) in Serang Regency. The method used is a normative juridical approach with analysis of laws and regulations, decision documents, and election law literature. The results of the study show that the Court consistently upholds the principles of electoral justice by making integrity and neutrality the main foundation in organizing Pilkada. This decision is also an important precedent in maintaining the quality of local democracy and emphasizing the limits to power intervention in electoral contestation